Trust in the police and authoritarian political attitudes in Latin America - Ferreira da Silva, Geélison; Ranulfo Felix de Melo, Carlos; Mendonça Lopes Ribeiro , Ludmila; Maradona Cortezzi Guimarães Pedras, Diego (Estudios Internacionales, 2023)
This article aims to explain trust in the police through an attitudinal approach that considers the effect of political attitudes, on the micro and macrossocial levels, on the dependent variable (trust in the police) with data from Lapop (2012) in 22 Latin American countries. The hypothesis is that in a context of low democratic quality and police inefficiency to guarantee public safety and limited respect for the law, it is possible for institutional trust to exist if citizens’ political attitudes are authoritarian. The effects of political attitudes are tested using the fixed effects model. The results confirm that political attitudes are important to explain trust in police and that the authoritarian attitudes analyzed had a positive impact on it in Latin America. The main contribution of the study is to identify a positive association between authoritarianism and institutional trust in the context of mishaps in democracy and police institutions.